Synthesis of Ultrafine Intermetallic Particles by the Vapor-Phase Coreduction of Metal Chlorides with Hydrogen - S. PalDey; H. Y. Sohn (The Minerals, Metals and Materials Society, 1998)
"Fine particles of nickel aluminides and Ni4Mo were synthesized by reducing mixtures of, respectively, A1Cl3 + NiC12 and NiC12 + MoC12 vapors with hydrogen. Though thermodynamically favorable, the coreduction of NiC12 and A1Cl3 by H2 to form Ni3Al did not readily happen experimentally. The addition of a small amount of aluminum vapor was needed to initiate the coreduction reaction. The product particles as observed by TEM were very fine but usually agglomerated. The electron diffraction pattern of particles identified NiAl and NiA13 along with Ni3Al and metallic Ni. The content of Ni3Al was maximized at 52 mol% at 1050°C under the partial pressures ofH2, A1Cl3, and NiC12 at 57, 1.4, and 0.5 kPa, respectively. When a mixture of NiC12 + MoC15 was reduced by hydrogen, Ni4Mo particles with some Ni or Mo particles were obtained, the maximum content of Ni4Mo obtained being 93 mol % . The particle size was in the range of 100 to 200 nm. An Ni4Mo coating of 700 nm thickness on an Ni substrate was also prepared.IntroductionThe search for new high-temperature structural materials has stimulated much research on intermetallic compounds. Nickel aluminides have low densities, relatively high melting points, and good high-temperature strength properties. They show an increase, rather than a decrease, in yield strength with increasing temperature (1). Ni4Mo is also of interest as a high-temperature structural material. The major shortcomings of these intermetallics are their inherent brittleness at room temperature when they are in polycrystalline form. For much the same reason, the conventional casting of intermetallics is difficult. Ingot metallurgy and powder metallurgy are two other processing techniques. The first technique is quite energy consuming. In powder metallurgy, the powders of metals and alloys are consolidated in near net shape and then subjected to secondary processing. It would, therefore, be advantageous if intermetallic compounds can be produced in fine powder form from inexpensive raw materials, using less energy."